Heterogeneous influence of neighborhood features on community satisfaction: a comparative study in Beijing’s urban and suburban communities - Jiang, Huaxiong; Cai, Runting; Yang, Ding; Huang, Zhuo; Song, Jinping (Frontiers in Public Health, 2023)
Introduction Community satisfaction contributes to urban planning, community development, and policy formulation. Yet, we lack comprehensive knowledge about how different neighborhood features impact satisfaction, especially across diverse community types. Methods Relied on a sample of 4,009 respondents in Beijing, this study examines the influence of neighborhood features on community satisfaction through neighborly interactions, focusing on the heterogeneity between urban and suburban communities, using structural equation models. Results The results reveal that community service and community management exert significant influences on community satisfaction, primarily mediated by the role of neighborly interactions. Then, transportation convenience positively influences community satisfaction in urban areas, while no housing property has a negative effect in suburban communities. Discussion These results highlight varied neighborhood effects on community satisfaction, informing tailored urban planning and policies that address unique traits and requirements of different communities.